(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A household survey was conducted in a preselected rural area (279 households) of Mymensingh district in Bangladesh to know the overall production and husbandry practices regarding indigenous ruminant farming and their future outlook. Data were analyzed following descriptive statistics. The average cattle (144 HHs) and goat (63 HHs) distribution per household were 1.83 and 2.14, respectively. Daily milk production of cattle and goat recorded 1.47 and 0.24 liters including the lactation period 201.98 and 87.21 days. Most of the farmers housed their cattle (88.19%) and goat (55.55%) outside the dwelling. Only 2.08% farmers purchased feed for cattle. Natural and uncontrolled breeding observed for all ruminants in the studied area. Digestive disorder (blot) in cattle (12.50%) and goat (14.29%) identified as one of the major problems in the studied areas. Vaccination practice followed very limited owners of cattle (19.44%) and goat (4.76%). Proper initiative, funding, farm-based training to educated farmers including modern animal husbandry practices could increase indigenous ruminant population in the rural area of Bangladesh. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 552-556